PLC design for automatic power transfer of 11kv switchgear - Wahid, Herman; Omar, Azmi; Ismail, Mohd Fauzi; Ahmad, Nasarudin; Sahlan, Shafishuhaza; Mohamad, Elmy Johana; Abdul Wahab, Yasmin (Penerbit UTHM, 2022)
An Automated Transfer System (ATS) is to provide automatic power transfers to groups reloading loads from common sources, such as utility services, to alternative sources, such as standby generation, in the event of a normal source failure. The project aims to develop a new design of an automatic power transfer system for the 11kV switchgear. Using the basic building blocks of utility power, system topology, on-site generation, and uninterrupted power supply, the basic role of the automatic transfer system can now be determined. In this role, the Automatic Transfer System (ATS) must achieve two goals. First, the system must be stable where it should operate, even under abnormal power systems, without human intervention. Equally important, it must be able to distinguish when the system conditions do not guarantee transfer to alternate sources. Second, it must be able to control the switchgear as required and, in addition, be able to deliver accurate signal to the required alternative power sources (for example, to initiate start signal to the generator as soon as possible).